Dependence of the state of metabolism on the time of cessation of sports activities of former athletes - A.V. Elikov; M.M. Korosteleva; R.A. Khanferyan (Theory and Practice of Physical Culture, 2023)
Objective of the study was to study the main indicators of metabolism in the blood plasma of former athletes, depending on the time of completion of sports activities. Methods and structure of the study. The study involved 24 former male athletes, with various sports specializations, qualifications from III adult category to Candidates for Master of Sports, aged 19-29 years. Depending on the time of completion of an active sports career, former athletes were divided into two groups: those who completed sports for a period of up to two years and more than two years. The control group consisted of untrained men of the same age. Indicators of protein, carbohydrate, lipid, purine metabolism and oxidative balance were studied in blood plasma. Results and conclusions. The initial post-sport period is characterized by the predominance of catabolic processes (manifested in the form of a significant increase in the concentration of urea, medium molecular weight peptides, uric acid), carbohydrate metabolism disorders (a significant increase in glucose levels), lipid metabolism (a significant increase in total cholesterol, triacylglycerols) and oxidative balance in the form of accumulation TBA-active products against the background of a trend towards a decrease in total antioxidant activity. In the late post-sport period, there were no significant differences from the examined control group in terms of the studied indicators. The initial post-sport period is characterized by an unfavorable change in the indicators of all types of metabolism, followed by a reverse trend in the late post-sport period. A comprehensive study of key metabolic indicators is a reliable criterion for diagnosing the development of a state of detraining. Metabolic changes accompanying the development of the state of detraining are recommended to be taken into account in the interpretation of biochemical analyzes during the rehabilitation of former athletes.